2011
DOI: 10.1002/pssb.201147123
|View full text |Cite
|
Sign up to set email alerts
|

Composition and orientation dependence of the interfacial energy in Fe–Cr stainless steel alloys

Abstract: Using a first-principles quantum mechanical method, we calculated the (001) and (110) interfacial energies between the low temperature a and a 0 phases of Fe-Cr alloys as functions of chemical composition. We show that the interfacial energies and the interfacial energy anisotropy are highly composition dependent. In particular, the increasing interfacial energy anisotropy with decreasing compositional gap may induce different morphology of the decomposed phases for different compositions of the host alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…% chromium the layer structure changes into a single precipitate again with (110) facets. The appearance of (110) facets is in line with ab initio interface calculations [61] which show that the (110) interface has the lowest energy which compares well with the surface energies in Fig. 2.…”
Section: Monte Carlo Simulationssupporting
confidence: 85%
“…% chromium the layer structure changes into a single precipitate again with (110) facets. The appearance of (110) facets is in line with ab initio interface calculations [61] which show that the (110) interface has the lowest energy which compares well with the surface energies in Fig. 2.…”
Section: Monte Carlo Simulationssupporting
confidence: 85%
“…A group of researchers investigated Fe-Cr [90][91][92][93][94][95][96][97][98], Fe-Co [99,100], Fe-C [101,102] and Fe-Mn based alloys [103][104][105] by means of atom probe tomography, neutron diffraction, Mossbauer spectrometry, magnetic measurements, X-ray diffraction, transmission and scanning electron microscopy, electron diffraction, resistivity measurements and other techniques such as hardness and compression tests.…”
Section: Spinodal Decomposition In Fe-based Alloysmentioning
confidence: 99%
“…The static properties of the iron-chromium system have been extensively studied at the atomic level. For example, surface [7] and interface [8] energies and surface segregation energies of chromium [9] have been calculated for Fe-Cr alloys using ab initio methods. Importantly, such calculations have shown that the aforementioned critical Cr concentration for the onset of the corrosion resistance in stainless steels closely coincides with an onset of anomalous surface segregation of Cr in Fe-Cr alloys [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Their disagreement with ab initio calculations is succinctly demonstrated by inspecting the segregation of a Cr atom from the bulk to the surface of a bcc Fe crystal: all three semi-empirical models predict the Cr atom to segregate to the second layer of Fe atoms, whereas according to ab initio calculations the first layer (i.e., the surface itself) should be preferred [24]. In addition, all three models fail to reproduce the ab initio results of Fe-Cr interface energies [8]. As a consequence of these shortcomings, no Monte Carlo simulations of atom kinetics near Fe-Cr surfaces have been performed, and the current atomic-level knowledge of surface physics in Fe-Cr alloys is far from satisfactory, despite the practical importance of the topic in relation to the corrosion of steel surfaces.…”
Section: Introductionmentioning
confidence: 99%